Demand imbalances and multi-period public transport supply - Horcher,D; Graham,DJ (Transportation Research Part B: Methodological: an international journal, 2018)
This paper investigates multi-period public transport supply, i.e. networks in which capacity cannot be differentiated between links and time periods facing independent but nonidentical demand conditions. This setting is particularly relevant in public transport, as earlier findings on multi-period road supply cannot be applied when the user cost function, defined as the sum of waiting time and crowding costs, is nonhomogeneous. The presence of temporal, spatial and directional demand imbalances is unavoidable in a public transport network. It is not obvious, however, how the magnitude of demand imbalances may affect its economic and financial performance. We show in a simple back-haul setting with elastic demand, controlling for total willingness to pay in the network, that asymmetries in market size reduce the attainable social surplus of a service, while variety in maximum willingness to pay leads to higher aggregate social surplus and lower subsidy under efficient pricing. The analysis of multi-period supply sheds light on the relationship between urban structure, daily activity patterns, and public transport performance.